M1 polarization and the effect of PGE2 on TNF-α production by lymph node cells from dogs with visceral leishmaniasis - Venturin, G. L. [UNESP]; Chiku, V. M. [UNESP]; Silva, K. L.O. [UNESP]; de Almeida, B. F.M. [UNESP]; de Lima, V. M.F. [UNESP] (Wiley, 2016)
Canine visceral leishmaniasis (CVL) is caused by the intracellular parasite Leishmania infantum. Increased levels of arginase, nitric oxide (NO2) and prostaglandin E2 (PGE2) can play a regulatory role regarding the immune response in CVL cases. This study aimed to evaluate the arginase activity in adherent macrophages cultured from the lymph nodes of healthy and naturally infected dogs and to examine the NO2 and PGE2 levels in the supernatant of these cultures. In addition, the regulatory effect of PGE2 on the production of tumour necrosis factor (TNF-α) and interleukin-10 (IL-10) in supernatants from the total lymph node was observed in leucocyte cultures. The arginase activity was lower in the adherent macrophages cultured from the lymph nodes of naturally infected dogs and there were higher concentrations of NO2 and PGE2 in the supernatants of these cultures. Higher TNF-α and IL-10 concentrations were observed in supernatants from total lymph node leucocytes cultures, from infected dogs, and the presence of indomethacin only decreased TNF-α in the supernatant of these cultures. We conclude that the low arginase activity in macrophages suggested that M1 polarization and PGE2 were participating in the immune response and were increasing TNF-α in CVL.
Keywords: canine; cytokine; ELISA; Leishmania spp; macrophages